Medeia Negra (2018): black female body that sings and screams (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Medeia Negra (2018), conceived and performed by Marcia Lima, in Salvador, Bahia, based on the rewriting of the Greek myth, gives voice to the black female body, erased by the violence of colonization/slavery, in the invisibility of the penitentiary system. In this version she creates a character made up of phrases, experiences and testimony from women deprived of their freedom. The objective of this study is to review the concepts and scenic devices used to represent this forcibly silenced body, which returns transformed into fragments of stories, noises, screams, specters and songs.
Keywords: myth; theater; black female body